Land Use Changes on Traffic Generation: A Study in the Tallasa City Corridor - Akshari Tahir Lopa; M. Reza Hasrul; Jeddah Yanti (International Journal of Environment, Engineering and Education, 2022)
The objectives to be achieved in this study are to examine the effect of land-use change on traffic generation in the Tallasa City corridor in Makassar City. The goals to be completed are identifying land use and transportation conditions, calculating traffic flow, analyzing land use development, analyzing movement generation, and analyzing the effect of land-use change on traffic generation on the corridor of Tallasa City. The research method used in this research is descriptive by identifying the land use and transportation conditions of the Tallasa City corridor. Then carried out an analysis of land use development, analysis of generation and attraction, and analysis of the effect of land use on the generation and appeal of the Tallasa City corridor movement in Makassar City. Based on the analysis results, it can be concluded that the condition of average service level of the existing conditions on the Tallasa City corridor is in category A, with the meaning of stable flow, and the driver is free to determine the speed he chooses. The planned land use pattern in the study area is dominated by land use for housing, education, trade, and services. The type of land use influences the effect of land-use change on traffic generation in the Tallasa City corridor. As a result of this land-use change causes a generation that reduces the level of road services in the planning year, which changes to category C with the meaning of steady flow and speed controlled by traffic.